2005
DOI: 10.1002/app.22288
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of adsorption of anionic surfactants onto cationized lignocellulosic materials

Abstract: Cationized lignocellulosic materials (cotton fibers, wood sawdust, and maize-cob flour) are prepared by grafting quaternary ammonium groups for use as scavengers for anionic surfactants. Generally, rapid adsorption occurs and at saturation leads to a stoichiometric ratio of cationic sites and anionic surfactants such as sodium dodecyl sulfate, sodium dodecyl benzene sulfonate, and sodium oleate. Modeling of these adsorptions is tested using Langmuir, Freundlich, or Jossens equations, the latter giving the best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Agricultural by-products are promising sorbents due to their minimum cost and high sorption ability [5][6][7][8][9][10][11][12][13][14][15][16]. Biosorbents are prepared from naturally abundant waste biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural by-products are promising sorbents due to their minimum cost and high sorption ability [5][6][7][8][9][10][11][12][13][14][15][16]. Biosorbents are prepared from naturally abundant waste biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous reports explore adsorption of different anionic dyes to celluloses of varying cation content. [12][13][14] It has been shown that adsorption capacity reflects the degree of cationization of the cationic cellulose. The anionic dye used in this study is methyl orange, shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…H and 13 C NMR were recorded at room temperature using a Varian UNITY-400 and a Varian UNITY-500 spectrometer, respectively. FTIR spectra were recorded with a Perkin Elmer 16 PC FTIR spectrometer using the KBr technique.…”
mentioning
confidence: 99%
“…Igwe et al (2005) reported carboxymethylation and thiolation of coconut fiber and sawdust for the adsorption of lead, mercury and arsenic ions in water. Zghida et al (2006) reported the cationization of cotton fibers, wood sawdust and maize-cob flour for removing anionic surfactants from water.…”
Section: Introductionmentioning
confidence: 99%